Crises sécuritaires et socio-économiques au sahel : analyse des stratégies régionales et sous-régionales pour le maintien de la paix et de la sécurité - Abdouldjelil Mahamat Nour, Adam (My University, 2025)
Bu çalışma, Sahel bölgesindeki güvenlik ve sosyoekonomik krizleri inceler. Barışın sürdürülmesi için benimsenen bölgesel ve alt bölgesel stratejilerin etkililiğine odaklanır. Sahel’deki karmaşıklık, kurumsal zayıflık, iklim değişikliği etkileri ve dış aktörlerin etkisi gibi çoklu ve birbirine bağlı etkenlerden kaynaklanır. Yöntem, karşılaştırmalı ve disiplinlerarası bir çerçeveye dayanır. Akademik kaynaklar, kurumsal raporlar ve güncel istatistiksel veriler birlikte analiz edilir. Araştırma soruları iki başlıkta toplanır. Güvensizliğin temel nedenleri. Bölgesel yanıtların uygunluğu. Bulgular, yetersiz yönetişim ve sosyoekonomik dışlanmanın yerel toplulukların kırılganlığını artırdığını gösterir. Sürdürülebilir çözümler için yerel aktörlerin katılımı, topluluk dinamiklerinin dikkate alınması ve ulusal kapasitenin güçlendirilmesi gereklidir. Çalışma ayrıca, Sahel’in kültürel ve toplumsal özelliklerine saygılı ve duruma uyarlanmış bir uluslararası iş birliğinin zorunlu olduğunu vurgular.

This thesis provides an in-depth analysis of the security and socio-economic crises affecting the Sahel region, with a particular focus on the effectiveness of regional and sub-regional strategies for maintaining peace. It can be observed that the complexity of the Sahelian situation stems from multiple and interrelated factors, including institutional weaknesses, the effects of climate change, and the influence of external actors. The methodology adopts a comparative and multidisciplinary approach, combining the analysis of academic sources, institutional reports, and recent statistical data. The main research questions concern the identification of the root causes of insecurity and the assessment of the relevance of different regional responses. The findings highlight that deficient governance and socio-economic marginalization exacerbate the vulnerability of local populations. The study underlines the importance of involving local actors, taking community dynamics into account, and strengthening national capacities for the development of sustainable solutions. Finally, it emphasizes the necessity of adapting international cooperation to the cultural and social specificities of the Sahel.
Keywords: Ayaklanma; bölgesel stratejiler; cihatçılık; crisis management; development; devlet; governance; güvenlik krizleri; Güvenlik, Uluslararası; Insurgency; Islamic fundamentalism; international cooperation; İslami köktencilik; istikrar; jihadism; kalkınma; kriz yönetimi; local actors; regional strategies; Sahel; savaş; security crises; Security, International; socio-economic crises; sosyoekonomik krizler; stability; State; Terörizm; Terrorism; uluslararası işbirliği; war; yerel aktörler; yönetişim